The Determination of Alcohol in Wines by Means of Near Infrared Technology - Baumgarten, G.F. (South African Journal of Enology and Viticulture, 2017)
A rapid method for alcohol determination using Near Infra-red technology was investigated and compared to the standard pycnometric method. The apparatus was tested to show wine colour and sugar content had an influence on the analysis. The reproducibility of the technique was also checked and compared to that of the pycnometric method. It was found that colour, turbidity and sugar have little effect on the analysis and the reproducibility of the Near Infrared apparatus had a standard deviation of 0,04% as compared to the 0,06% of the pycnometer.